2019
DOI: 10.1093/humrep/dez126
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing identifies a GREB1L variant in a three-generation family with Müllerian and renal agenesis: a novel candidate gene in Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome. A case report

Abstract: The aetiology of Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome, characterized by uterovaginal agenesis in 46,XX women, remains poorly understood. Since familial occurrences are rare, genetic findings reported so far only apply to a minority of mainly sporadic cases and most studies have not included other family members enabling segregation analysis. Herein, we report on the investigation of a unique three-generation family of two female cousins with MRKH syndrome and unilateral renal agenesis (RA) and two de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 33 publications
4
41
0
2
Order By: Relevance
“…We also detected a maternal bias in the inheritance of GREB1L variants ( Table 2 ). This maternal bias has previously observed and two mechanisms have been suggested: (1) imprinting [ 8 , 36 ] (2) or GREB1L variants could affect male fertility resulting in a low rate of paternal inheritance [ 8 ]. Genital issues, including uterus aplasia, are common and have been reported in many females ( Table 2 ), but the presence in males may be underestimated as the defect might not be a gross morphological abnormality that causes infertility.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We also detected a maternal bias in the inheritance of GREB1L variants ( Table 2 ). This maternal bias has previously observed and two mechanisms have been suggested: (1) imprinting [ 8 , 36 ] (2) or GREB1L variants could affect male fertility resulting in a low rate of paternal inheritance [ 8 ]. Genital issues, including uterus aplasia, are common and have been reported in many females ( Table 2 ), but the presence in males may be underestimated as the defect might not be a gross morphological abnormality that causes infertility.…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports on disease-related GREB1L variants showed that a variable phenotype is present, including within families segregating the same variant (e.g., left vs. right ear) [ 36 , 37 ]. In addition, a high level of reduced penetrance has been reported, including in family 2 of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pan et al performed whole-genome sequencing (WGS) analysis of nine MRKH syndrome trios (patient and both parents) demonstrating the capacity of WGS in unbiased detection of de novo genomic variation [77]. Other recent studies also used NGS technology in genomic searches for genetic variation [24,64,78,79]. However, it remains a challenge to interpret the pathogenicity of these findings and investigations of larger cohorts will likely be needed in order to identify recurrent genetic variation.…”
Section: Embryology Etiology and Geneticsmentioning
confidence: 99%
“…In 2019, Herlin et al described whole-exome sequencing (WES) in a three-generation family with two female cousins having type II MRKH syndrome and unilateral renal agenesis, and two male relatives with renal agenesis. The study reported a co-segregating missense variant in GREB1L (Table 1) [24], a gene identified in 2017 to cause bilateral renal agenesis in fetuses of which several female fetuses also had uterus agenesis [73,74]. Just recently, Jacquinet et al reported four additional multiplex families with either type II MRKH syndrome or uterovaginal aplasia (fetuses) associated with renal malformations (agenesis in particular) in which pathogenic GREB1L variants were identified from WES data [72].…”
Section: Embryology Etiology and Geneticsmentioning
confidence: 99%
See 1 more Smart Citation